The “Love Hormone” Oxytocin Regulates the Loss and Gain of the Fat–Bone Relationship - Colaianni, Graziana; Sun, Li; Zaidi, Mone; Zallone, Alberta (Frontiers in Endocrinology, 2015)
The involvement of Oxytocin (OT) in bone metabolism is an interesting area of research that recently achieved remarkable results. Moreover, several lines of evidence have largely demonstrated that OT also participates in the regulation of energy metabolism. Hence, it has recently been determined that the posterior pituitary hormone OT directly regulates bone mass: mice lacking OT or OT receptor (OTR) display severe osteopenia, caused by impaired bone formation. OT administration normalizes ovariectomy-induced osteopenia, bone marrow adiposity, body weight and intra-abdominal fat depots in mice. This effect is mediated through inhibition of adipocyte precursor differentiation and reduction of adipocyte size. The exquisite role of OT in regulating the bone-fat connection adds another milestone to the biological evidence supporting the existence of a tight relationship between the adipose tissue and the skeleton.